Pubertal induction in Turner syndrome without gonadal function: A possibility of earlier, lower-dose estrogen therapy - Hasegawa, Yukihiro; Hasegawa, Tomonobu; Satoh, Mari; Ikegawa, Kento; Itonaga, Tomoyo; Mitani-Konno, Marie; Kawai, Masanobu (Frontiers in Endocrinology, 2023)
Delayed/absent puberty and infertility in Turner syndrome (TS) are due to primary hypogonadism. More than 80% of patients with this syndrome who are followed at hospitals during childhood will not experience regular menstruation. Indeed, estrogen replacement therapy (ERT) is needed before young adulthood for nearly all patients with TS. Historically, there is a well-established maintenance method of ERT in adults, but ERT as pubertal induction in children is only beginning to be explored. The present manuscript aimed to review past and current induction therapies for patients with TS without endogenous estrogen production, starting with background knowledge. There are a lot of issues to be elucidated on how to induce puberty in TS such as when and how to start ERT, and how to increase the dosage of estrogen.　An ideal, pubertal induction therapy using a transdermal estradiol patch mimicking physiological estradiol increment is suggested, although the evidence to support this therapy is still pending.